Analisis Yuridis Penegakan Hukum Terhadap Penyalahgunaan Lampu Strobo Dan Sirene Berdasarkan Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas Dan Angkutan Jalan - Candra Agus Surya Prayogi (Indonesian Journal Publisher, 2026)
This study aims to analyze the legal regulation concerning the use of strobe lights and sirens on motor vehicles and to examine law enforcement against misuse by unauthorized parties under Indonesian traffic law. The research employs a normative juridical method using statutory and conceptual approaches. Primary legal materials consist of Law Number 22 of 2009 concerning Road Traffic and Transportation and its implementing regulations, while secondary legal materials are derived from legal literature, journals, and relevant legal doctrines. The findings indicate that the use of strobe lights and sirens is legally restricted to specific vehicles performing emergency duties, state functions, and other authorized public services. Unauthorized use by civilians, including individuals escorting ambulances for humanitarian purposes, constitutes a violation of traffic law and may result in administrative and criminal sanctions. Law enforcement remains essential to uphold legal certainty, ensure road safety, and maintain public order in traffic management. The study concludes that humanitarian motives cannot justify unlawful use of traffic priority facilities because the principle of legality remains the primary foundation in regulating road traffic governance and public safety.